PENGGUNAAN MEDIA POWER POINT TERHADAP MOTIVASI BELAJAR SISWA KELAS XI DI SMA NEGERI 8 SELAYAR - Ani; Kasman; Akram (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Effect of PowerPoint Media Use on Student Learning Motivation in Natural Science Subjects for Grade XI Students at SMA Negeri 8 Selayar. Thesis, Educational Technology Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I Dr. Kasman S.Pd, M.Pd and Supervisor II Akram, S.Pd, M.Pd. This study aims to determine the effect of PowerPoint media use on student learning motivation in natural science subjects for grade XI students at SMA Negeri 8 Selayar. This study used a quantitative approach with an ex-post-facto design. The population in this study was all 36 grade XI students, and the entire population served as the research sample. Data collection techniques used were observation, questionnaires, and documentation. The independent variable in this study was PowerPoint use, while the dependent variable was student learning motivation. Observation results showed that student learning motivation activities were in the good category, with an average percentage of 79.83%. Observations on the use of PowerPoint in learning showed a very good rating, with an average percentage of 91.80%. This indicates that students felt helped in understanding the material through engaging and interactive visual displays. Questionnaire results on the student learning motivation indicator indicated that students felt more active, focused, disciplined, and enthusiastic during the learning process.A statistically inferential analysis using the Pearson correlation test showed a significance value of 0.000 < 0.05, thus Hₐ was accepted and H₀ was rejected. This indicates a significant effect between the use of PowerPoint media on student learning motivation in science for grade 11 at SMA Negeri 8 Selayar. herefore, it can be concluded that the use of PowerPoint media plays a significant role in increasing student learning motivation, and teachers are advised to continue utilizing this medium in the learning process.